Seroprevalence of anti-Leishmania spp. antibodies in rural dogs from the city of Monte Negro, State of Rondônia, Brazil - Aguiar, Daniel M.; Oliveira, Trícia Maria F. de Sousa [UNESP]; Cavalcante, Guacyara T.; Labruna, Marcelo B.; Camargo, Luis Marcelo A.; Machado, Rosangela Z. [UNESP]; Gennari, Solange M. (Colégio Brasileiro de Parasitologia Veterinária, 2010)
O presente estudo determinou a prevalência de anticorpos anti-Leishmania spp. em cães do município de Monte Negro, Estado de Rondônia, Brasil. Foram utilizados os testes de ELISA (NE > 3) e RIFI (>1:40) para avaliar 161 amostras de soro de cães da zona rural do município. Quarenta e cinco cães (27,9%) reagiram no teste de ELISA e cinco (3,1%) na RIFI. O presente estudo demonstra pela primeira vez a freqüência de exposição por Leishmania spp. em cães de Rondônia, Região Amazônica.

The present study assessed the prevalence of anti-Leishmania spp. antibodies in dogs from the city of Monte Negro, State of Rondônia, Brazil. ELISA (NE > 3) and IFAT (>1:40) were used to evaluate 161 serum samples collected from rural dogs from Monte Negro. Forty-five (27.9%) dogs were positive by ELISA tests and five (3.1%) were positive by IFAT. The present study showed for the first time the frequency of exposure to Leishmania spp. in dogs in the State of Rondônia, Amazon Region.
Soroprevalência de anticorpos anti-Leishmania spp. em cães rurais do município de Monte Negro, Estado de Rondônia, Brasil
Keywords: Leishmania spp.; Prevalence; Dog; ELISA; IFAT; Leishmania spp.; Prevalência; Cão; ELISA; RIFI